Increased Throwing Accuracy Improves Children's Catching Performance in a Ball-Catching Task from the Movement Assessment Battery (MABC-2) - Dirksen, Tim; De Lussanet, Marc H. E.; Zentgraf, Karen; Slupinski, Lena; Wagner, Heiko (Frontiers in Psychology, 2016)
The Movement Assessment Battery for Children (MABC-2) is a functional test for identifying deficits in the motor performance of children. The test contains a ball-catching task that requires the children to catch a self-thrown ball with one hand. As the task can be executed with a variety of different catching strategies, it is assumed that the task success can also vary considerably. Even though it is not clear, whether the performance merely de-pends on the catching skills or also to some extent on the throwing skills, the M-ABC2 takes into account only the movement outcome. Therefore, the purpose of the current study was to examine 1) to what extent the throwing accuracy has an effect on the children's catching performance and 2) to what extent the throwing accuracy influences their choice of catching strategy. In line with the test manual, the children's catching performance was quantified on basis of the number of correctly caught balls. The throwing accuracy and the catching strat-egy were quantified by applying a kinematic analysis on the ball's trajectory and the hand movements. Based on linear regression analyses, we then investigated the relation between throwing accuracy, catching performance and catching strategy. The results show that an increased throwing accuracy is significantly correlated with an increased catching performance. Moreover, a higher throwing accuracy is significantly correlated with a longer duration of the hand on the ball’s parabola, which indicates that throwing the ball more accurately could enable the children to effectively reduce the re-quirements on temporal precision. As the children's catching performance and their choice of catching strategy in the ball-catching task of the M-ABC2 are substantially determined by their throwing accuracy, the test evaluation should not be based on the movement outcome alone, but should also take into account the children's throwing performance. Our findings could be of particular value for the development of simple but informative catching assessments, and may provide addi-tional insights into the causes of performance deficits in ball catching.